STUDI SIFAT FISIS DAN MEKANISPADA SOLIDIFIKASI BESI COR KELABU DALAMCETAKAN PERMANEN UNTUK TAPPING AKHIR - SUPRIYANTO, HERI; , Ir. H. Masyrukan, MT (2016)
This research took a part of metal casting, that was a matter of melting which aimed at knowing the influene of the melting of grey cast iron in the final tapping with a high frequency induction on the values of hardness, micro structure and chemical composition. This research was conducted on the specimen of greay cast iron testing from a permantent mold. The testings conducted were a testing of chemical composition using spectrometer, a testing of hardness through the rockwell method using a hardness testinger converted into the hardness brinell method, and the testing of micro structure using a metalography microscope. From the results of the testing of specimen, it was obtained that the bahwa specimen of grey cast iron has several chemical composition, they were: carbon (C): 3.52%, silicon (Si): 1.95%, manganese (Mn): 0.,470%, etc. The hardness testing was conducted on two sides: the upper-part testing and the side part testing, each had 5 testing points. In the side part, it was obtained the hardness values (223,79; 226,97; 224,12; 232,44; 227,03). it was obtained the average hardness value as much as 226,02. In the upper-part, it was obtained the hardness value (441,14; 432,50; 430,32; 439,58; 425,86) and the average value 433,12